(3GdGcJaG aj eZGRj GdeUWai hGdKdGKI GdNdaGs - (3GdcdGYj , SdjeGf Hf ehSi Hf SGde Hf MSGf GdMejQj, CHh GdQHjY,J (B634 (3g` s
(3ChdgG (B:s
(3gPG cJGH PgHJ ajg Edi GjbGY GdEbfGY hGeJGY GdfahS hGdGSeGY HGJSGb GdNHQ Yf SjQI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
((3jG CjgG GdPjf CefhG EPG LGAce GdeDefGJ egGQLGJ aGeJMfhgf Gddg GYde HGjeGfgf aGf YdeJehgf eDefGJ adG JQLYhfgf Edi GdcaGQ GdBjI (B) (3Je GdGcJaGA s
(3fSNI KGfjI ef GdLRA GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B136 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B399s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B28 s
Keywords: (3GdJGQjNs